2007
DOI: 10.1007/s12016-007-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Syndrome and Cancer

Abstract: Thrombosis is a frequent complication of cancer that is a substantial cause of morbidity and mortality. The association of antiphospholipid antibodies (aPL) and cancer has been under investigation for several years. Recent findings suggest an increased prevalence of certain cancers in aPL-positive patients; thus, an intensive search for an occult malignancy is prompted in these patients. In addition, several studies reported on elevated levels of aPL in various malignancies; it seems, however, that aPL levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…In addition, several studies reported on elevated levels of aPL antibodies in various malignancies. 43 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies reported on elevated levels of aPL antibodies in various malignancies. 43 …”
Section: Discussionmentioning
confidence: 99%
“…These antibodies have been found in association with many malignancies, particularly hematological malignancies including lymphomas, acute myeloid leukaemia, chronic myelocytic leukemia and lymphoproliferative disorders [16,28].…”
Section: Discussionmentioning
confidence: 99%
“…The increased incidence of antibodies in the aged (including aPL, rheumatoid factor, ANA) suggest that there is an age‐related impaired immune system . aPL antibodies have been described in elderly patients with several diseases, such as long‐term medication, advanced renal or hepatic failure, giant‐cell arteritis, infections and especially cancer .…”
Section: Discussionmentioning
confidence: 99%